2014
DOI: 10.1007/s10965-014-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

Processable aromatic polyesters based on bisphenol derived from cashew nut shell liquid: synthesis and characterization

Abstract: A new bisphenol viz., 4-(4-hydroxyphenoxy)-3-pentadecylphenol (HPPDP) was synthesized starting from cashew nut shell liquid (CNSL). Aromatic (co)polyesters containing ether linkages in the main chain and pendent pentadecyl chains were synthesized by the interfacial polycondensation of HPPDP with terephthalic acid chloride (TPC), isophthalic acid chloride (IPC) and a mixture of TPC and IPC (50:50 mol %) and by polycondenation of varying composition of HPPDP and bisphenol-A (BPA) with TPC. The resultant (co)poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 35 publications
(38 reference statements)
0
21
0
Order By: Relevance
“…As previously mentioned, biobased bisphenols were recently utilized for the preparation of polyesters . Past studies from our laboratory showed that BG could be successfully used to prepare epoxy thermosets and polycarbonates characterized as having good thermomechanical properties .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…As previously mentioned, biobased bisphenols were recently utilized for the preparation of polyesters . Past studies from our laboratory showed that BG could be successfully used to prepare epoxy thermosets and polycarbonates characterized as having good thermomechanical properties .…”
Section: Introductionmentioning
confidence: 97%
“…Additionally, it was shown that the barrier properties of FDCA‐containing polyesters are substantially higher than those of PET, whereas the mechanical properties are essentially equivalent to those of their TPA‐based counterparts . In a similar way, the use of biobased bisphenols for the preparation of polyesters has been widely studied and has shown promising preliminary results . Thus, there is no doubt that studies involving the use of new biobased aromatic diols and/or diacids for the preparation of thermosets and thermoplastics are topical and timely …”
Section: Introductionmentioning
confidence: 99%
“…The flexibilizing ether moieties are expected to impart melt‐processing characteristics to polyimides, as is the effect of the pentadecyl chains. To this end, we designed and synthesized a new aromatic diamine, namely 4‐(4‐(4‐(4‐aminophenoxy)‐2‐pentadecylphenoxy)phenoxy)aniline (APPPA), starting from 4‐(4‐hydroxyphenoxy)‐3‐pentadecylphenol (HPPDP) which in turn was obtained using cashew nut shell liquid as the starting material . Polyetherimides were synthesized by polycondensation of APPPA with 3,3′,4,4′‐oxydiphthalic anhydride (ODPA), 4,4′‐(hexafluoroisopropylidene)diphthalic anhydride (6‐FDA) and 3,3′,4,4′‐biphenyltetracarboxylic dianhydride (BPDA) using a one‐step high‐temperature solution method.…”
Section: Introductionmentioning
confidence: 99%
“…Yield 56 g (90%). Melting point 40 °C (literature value 40 °C). IR (cm −1 ): 801 (C − Br stretching), 1243 (Ar − O − C stretching).…”
Section: Methodsmentioning
confidence: 99%